2021
DOI: 10.1101/2021.10.27.466053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell RNA sequencing unveils intestinal eosinophil development and specialization

Abstract: Eosinophils are an integral part of the gastrointestinal (GI) immune system that contribute to homeostatic and inflammatory processes. Here, we investigated the existence of functional subsets that carry out specialized tasks in health and disease. We used single-cell transcriptomics and high-dimensional flow cytometry to delineate murine eosinophil subpopulations and their ontogenetic relationship in the steady state and during infection and inflammation. Profiling of eosinophils from bone marrow, blood, sple… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…These markers are associated with eosinophil activation in response to intestinal inflammation (Arnold et al, 2018;Griseri et al, 2015), indicating that microbial colonization regulates the activation and/or maturation of intestinal eosinophils. Single-cell RNA-seq of murine eosinophils also indicated that eosinophil maturation in the gut is driven by microbiota-derived signals (Gurtner et al, 2021). Taken together, our results show that eosinophils respond to microbial colonization and play a critical role in facilitating homeostatic host-microbiota crosstalk by maintaining barrier integrity and regulating microbiota-dependent changes in intestinal physiology.…”
Section: Articlementioning
confidence: 53%
“…These markers are associated with eosinophil activation in response to intestinal inflammation (Arnold et al, 2018;Griseri et al, 2015), indicating that microbial colonization regulates the activation and/or maturation of intestinal eosinophils. Single-cell RNA-seq of murine eosinophils also indicated that eosinophil maturation in the gut is driven by microbiota-derived signals (Gurtner et al, 2021). Taken together, our results show that eosinophils respond to microbial colonization and play a critical role in facilitating homeostatic host-microbiota crosstalk by maintaining barrier integrity and regulating microbiota-dependent changes in intestinal physiology.…”
Section: Articlementioning
confidence: 53%
“…This suggests that AHR-deficient eosinophils have a diminished ability to promote regulatory T cell differentiation. A previous study found that eosinophils suppress Th1 cells through PD-L1 (CD274; Arnold et al, 2018 ), and a recent preprint paper described a subset of CD80 + CD274 + eosinophils with high Ahr expression ( Gurtner et al, 2021 Preprint ). We found that this CD80 + CD724 + eosinophil subset was not affected by AHR deficiency ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to WT eosinophils, those from IL-5Tg hearts expressed lower levels of CD101 and CD62L, a marker of tissue-resident lung eosinophils that is reduced in inflammatory eosinophils 29 ( Figures 5 E and 5F). PDL1 expression, shown to increase after bacterial infection, 30 was higher in IL-5Tg eosinophils ( Figure 5 G). Overall, this shows that cardiac eosinophils from IL-5Tg mice display an activated phenotype.…”
Section: Resultsmentioning
confidence: 90%